Agresi Verbal pada Remaja Penggemar K-Pop NCT: Adakah hubungan dengan Celebrity Worship dan Psychological Well-being - Mahardhika, Lussy; Santi, Dyan Evita; Ananta, Aliffia (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to explore the relationship between celebrity worship, psychological well-being, and verbal aggression in adolescent K-Pop NCT fans. Verbal aggression refers to behavior that intends to hurt, intimidate, or harm someone verbally or physically. Verbal aggression includes the use of mocking words, abusive language, expressions of hatred, and sarcasm. This study uses quantitative methods involving a population of 205 K-Pop NCT fans who are members of the